A general strategy for the functionalization of two-dimensional metal chalcogenides. Issue 22 (30th May 2018) - Shen, Jianfeng; Wang, He; Zhuang, Peiyuan; Zeng, Haotian; Ge, Yuancai; Steven, Craig; Dong, Pei; Gao, Shang-Peng; Ye, Mingxin
Abstract : A simple and universal functionalization route for two-dimensional metal chalcogenides is demonstrated. Abstract : Two-dimensional (2D) metal chalcogenides (MC) such as MoS2 have been recognized as promising materials for near future applications. However, general strategies to functionalize them are still scarce, while the nature of functionalization still remains unclear. Herein, we demonstrate a simple and universal functionalization route through complexation reaction between the amino-containing organic agents and MCs. Degrees of functionalization are tunable by adjusting the organic group types and ratios. No further defects are introduced and the functionalized 2D MCs are dispersible in corresponding typical solvents. Both experimental results and geometry optimization calculations indicate that the grafting of functional groups through the coordination effect truly exist, while the surface properties and resulting photoelectric properties of 2D MCs are greatly altered. More intriguingly, our proposed functionalization process is demonstrated to be universal and can be applied to different MCs, thus opening new avenues for the application of 2D MCs.